(untitled) (Zaporizhzhia Historical Review, 2021)
None of credit-bank institutions of the Russian empire causeed such a sharp criticism in the literature of the late ХІХ ñ early XX century as the Peasant land bank. Among contemporaries negative estimations of the Peasant land bank prevailed. Supporters of rendering assistance to peasants noticed only slow development of bank operations, and their opponents approved that the bankís activities were but harmful for agriculture as a whole. Each of the authors stated the ideas concerning the purposes, problems and the organizations of work in the bank.